Are Cities the New Growth Escalator? - Moretti, Enrico (World Bank, Washington, DC, 2014)
Urban areas tend to have much more productive labor and higher salaries than rural areas, and there are vast differences across urban areas. Areas with high salaries and high productivity tend to have employers that invest in much more research and development than areas with low salaries and low productivity. This paper addresses two questions. First, it discusses the causes of these vast geographical differences in wages, human capital, and innovation. The second part of the paper discusses regional economic development policies. The European Union has an even more ambitious program transferring its development funds to regions with below average incomes. Asian countries, especially China, have a variety of special economic zones, designed to attract foreign investment to specific areas. Such regional development policies, often called place-based economic policies, are effectively a form of welfare, targeting cities or regions, not individuals. While such policies are widespread, the economic logic behind them is rarely discussed and even less frequently understood. This paper clarifies when these policies are wasteful, when they are efficient, and who the expected winners and losers are. Understanding when government intervention makes sense and when it does not is a crucial first step in setting sound economic development policies. Local governments can certainly lay a foundation for economic development and create all the conditions necessary for a city's rebirth, including a business climate friendly to job creation.